Navigation bronchoscopy-guided radiofrequency ablation for nonsurgical peripheral pulmonary tumors - Xie, Fangfang; Herth, Felix (Respiration, 2017)
We have recently developed a flexible catheter electrode used for bronchoscopic radiofrequency ablation (RFA). Two patients with nonsurgical stage IA peripheral lung cancer and 1 with lung metastasis underwent treatment with flexible catheter RFA utilizing navigation bronchoscopy. Chest computed tomography (CT) and positron emission tomography/CT (PET/CT) were performed before and after RFA to assess the ablation response of the patients. One patient's tumor had no prior PET uptake and therefore no follow-up PET was obtained. The first and the third patient obtained partial response to RFA, and the second patient obtained complete response 3 months after RFA. The first patient developed progressive disease 6 months after RFA. The second and the third patient achieved one-year progression-free survival. No significant complications occurred in the 3 patients. Navigation bronchoscopy-guided RFA is a safe and feasible procedure for poor surgical candidates with stage IA lung cancer or lung metastasis.
Published online: July 06, 2017
Gesehen am 22.10.2018